ФУНКЦІОНАЛЬНІСТЬ ПЕРЕДМОВИ В ЦІЛІСНОМУ СПРИЙНЯТТІ ТЕКСТУ (ВІТОЛЬД ҐОМБРОВИЧ „ТРАНС-АТЛАНТИК”) - Тичініна, Альона Романівна (Чернівецький національний університет, 2017)
Розглядаються особливості функціонування паратексту, зокрема його рецептивна складова. Акцентується його участь в оформленні тексту у специфічну інтерпретаційну рамку цілісності, що генерує механізм рецептивної дії, звужує чи розширює горизонт очікування читача. Підкреслюється роль авторської передмови в архітектоніці літературного тексту як певною мірою „проксемічного центруˮ. За результатами рецептивного опитування стосовно роману Вітольда Ґомбровича (1904–1969) „ТрансАтлантик” (1953) функція передмови інтерпретується як діалогічна. На основі аналізу трьох авторських передмов (1951, 1953, 1957) і матеріалів письменницького щоденника робиться висновок про наративну динаміку цих передмов і безпосередній вплив означеного паратекстуального фрагмента тексту на процес декодування змісту роману
The methodology of detection of paratextual connections detailed by Gerard Genette is analyzed. It is proved that such at first sight peripheral elements of a text are able not only to frame it specifically but also to make possible its transformation into a book. It is emphasized that paratextual modi respectively generate the mechanism of receptive action, narrow or/and broaden the expectation horizon of a reader. Subsequently, adjusted by the experience, they form a different perspective of perception which nevertheless is restricted and emphasized by a kind of paratextual “frame” that is sometimes called the interpretational one. An author's foreword is a sort of proxemic center in architectonics of literary text. The main function of the textual threshold that can be created directly by an author, publisher, and other writer is to inform readers about circumstances the text was written under, stages of creation, interpretation of important or complicated (from the standpoint of the author) moments of the text, its conception, genre, biographic motives that guide a reader's reception in one way or another In line with the historical poetry considering a text with a few author's prefaces is the most effective way. Three prefaces (1951, 1953, 1957) to the novel “TransAtlantic” (1953) by the Polish writer-immigrant Witold Gombrowicz (1904–1969) have become the subject of the analysis. Obviously, the specifics of narration in the aforementioned prefaces appear interesting. Not only is the experimental character of Gombrowicz's shape proved but also the dynamics of his texts' content in the historical time. Proofs of that, apart from the prefaces, are found in his diaries. The function of the author's preface has the exceptional receptive weight as it directs the reader's receptions only to the indicated destination and establishes the profound contact, more precisely the dialog, with a reader. Serving as an interpretative frame that outlines an author's interpretation of the text, in this case a preface is capable not only of forming but also deforming the reader's expectation horizon.
Keywords: паратекстуальність, передмова, наратор, рецепція, горизонт очікування, В. Ґомбрович, „Транс-Атлантик”